Quantitative Assessment of Photoneutron-induced Secondary Radiation Dose in Prostate Treatment Using an 18 MV Medical Linear Accelerator: A Monte Carlo Study - Mustapha Assalmi; Abdullah Alshreef; EL Yamani Diaf; Assia Arectout; Nicholas Ade; El Hassan El Berhdadi (Journal of Medical Physics)
Purpose: This study aims to quantify the secondary radiation dose caused by photoneutrons during prostate cancer treatment using an 18 MV medical linear accelerator (LINAC) through Monte Carlo simulations and experimental validation. Methods: Monte Carlo simulations were performed using G4Linac_MT to model the 18 MV photon beam of an Elekta LINAC. The simulation results were validated against experimental measurements. Neutron characteristics, including penetration, cross-section interactions, Linear Energy Transfer (LET), and dose contributions, were analyzed using an adult male ICRP phantom. Prostate treatment scenarios involved 3D-CRT plans with 4-fields, 5-fields, and 7-fields. Specific absorbed fractions (SAFs) in various organs were also evaluated. Results: Simulation and experimental measurements showed strong agreement, with a dose error of approximately 0.74%, and 97% of dose points passed a 2%/2 mm gamma index. Intermediate neutrons constituted 87.05%, while 12.95% were fast neutrons. Neutron dose contributions were 0.63%, 0.33%, and 0.77% for the 3D-CRT 4-field, 5-field, and 7-field plans, respectively. SAF values decreased as neutron energy increased, highlighting reduced neutron interaction efficiency at higher energies. Conclusions: Monte Carlo simulation is a reliable approach for evaluating neutron dose contributions in high-energy X-ray LINACs. Optimization of treatment plans is essential to minimize neutron-induced dose contributions.